AN ANALYSIS OF IMAGERY IN THREE SELECTED POETRIES FROM COMPLETE POEMS OF ROBERT FROST - Safnidar Siahaan; Novita Elisabeth Mbaru (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
This research analyzes imagery in Robert Frost selected poetry. This research aimed to find out what are the types of imagery and how many imageries used by Robert Frost in selected poetry, they are “Lost in Heaven”, “Desert Places” and “Leaves compared with Flower” based on the theory of Sayuti (2010) for analyzing the types of imagery. There are six types of imagery according to Sayuti namely visual imagery, auditory imagery, olfactory imagery, gustatory imagery, kinesthetic imagery, and tactile imagery. Then, the data were analyzed by using the qualitative descriptive method. This research found visual imagery, auditory imagery, kinesthetic imagery, and tactile imagery, which are presented in twenty- seven (27) data from three poems. The researcher found 27 data categorized into types of imagery, which consist of 13 visual images, 11 kinesthetic images, 2 auditory images, 1 tactile image. Robert Frost mostly uses visual imagery in selected poems.